Analisis Kurikulum Merdeka Belajar Dalam Memfasilitasi Pembelajaran Abad Ke-21 Pada Siswa Menengah Atas - Sri Hanipah (Jurnal Bintang Pendidikan Indonesia, 2023)
The independent curriculum is an educational approach that aims to provide independence to students in their learning so that they can optimally develop their potential. In the era of globalization and the rapid development of information technology, 21st-century learning is an urgent need. This research aims to describe the role of the independent learning curriculum in facilitating 21st-century learning in senior high schools. The method used in this research is descriptive-qualitative with a case study design. The research was conducted at SMAN 2, Merekau, South Papua. Data collection techniques used in this research include in-depth interviews, observation, and documentation. The results showed that: 1) the independent learning curriculum for facilitating 21st century learning is good. It is proven that the learning tools of SMAN 2 Merauke have successfully integrated 21st century skills (collaboration, communication, critical thinking, creativity, character, and citizenship) into the learning tools. 2) The role of the principal and teachers: The principal as the person in charge and teachers as the implementers of learning play an important role in the successful implementation of an independent curriculum with 21st century skills.